Keeping our Students Safe: Teacher’s Responsibility - Starrett, Teresa Martin; Fredrickson, Rebecca (Advances in Social Sciences Research Journal, 2015)
During their lunch period, a second grade student began choking on his sandwich. A teacher noticed the student choking and walked with him to the office on the other side of the school. When the student and teacher got to the office, the school secretary performed CPR but the student had already passed out. 911 was called while the secretary continued to perform CPR. When the ambulance arrived, the EMTs also performed CPR and the student was taken to the hospital where he was pronounced dead. When interviewed by the police and district personnel, the teacher who had escorted the student to the office said she did not perform the Heimlich maneuver because she had just discovered she was pregnant.